2006
DOI: 10.1002/jnr.20870
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of microglia activation induced by amyloid‐beta and prion peptides: Role in neurodegeneration

Abstract: The inflammatory responses in Alzheimer's disease (AD) and prion-related encephalopathies (PRE) are dominated by microglia activation. Several studies have reported that the amyloid-beta (Abeta) peptides, which are associated with AD, and the pathogenic isoform of prion protein (PrPSc) have a crucial role in neuronal death and gliosis that occur in both of these disorders. In this study, we investigate whether Abeta and PrPSc cause microglia activation per se and whether these amyloidogenic peptides differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…Microglia are known to express some of the same LRP receptors (Laporte et al 2004), which may provide a mechanism facilitating the action of MT upon microglia. Indeed it is well established that betaamyloid is internalised by microglia via interaction with LRP receptors (Laporte et al 2004), and that beta-amyloid induces reactive microglial phenotypes (Floden and Combs 2006;Garção et al 2006). Alternatively, Kauppinen et al (2008) have unexpectedly reported that zinc can directly induce microglial reactivity, and it is well established that extracellular levels of zinc are increased following traumatic brain injury (Choi and Koh 1998).…”
Section: Discussionmentioning
confidence: 94%
“…Microglia are known to express some of the same LRP receptors (Laporte et al 2004), which may provide a mechanism facilitating the action of MT upon microglia. Indeed it is well established that betaamyloid is internalised by microglia via interaction with LRP receptors (Laporte et al 2004), and that beta-amyloid induces reactive microglial phenotypes (Floden and Combs 2006;Garção et al 2006). Alternatively, Kauppinen et al (2008) have unexpectedly reported that zinc can directly induce microglial reactivity, and it is well established that extracellular levels of zinc are increased following traumatic brain injury (Choi and Koh 1998).…”
Section: Discussionmentioning
confidence: 94%
“…Experiments were conducted with final peptide concentrations of 5 mM [18]. PrP 106 -126 (KTNMKHMAGAAA AGAVVGGLG) and scramble PrP (Scr, AVGMHAGKG LANTAKAGAMVG) were purchased from Sangon BioTech (Shanghai, China) and dissolved in sterile PBS to a concentration of 1 mM and left to aggregate at 378C for 12 h. The experiments were conducted with final peptide concentrations of 50 mM [18,19].…”
Section: Methodsmentioning
confidence: 99%
“…Primary microglial cell cultures were obtained from neonatal Wistar rats 5–7 days old, according to the method described by Garcao et al [9]. After sterilization with 75% ethanol for 3–5 min, the brain was dissected and the meninges were carefully removed under a stereomicroscope.…”
Section: Methodsmentioning
confidence: 99%
“…Mounting evidences also indicate that microglial activation contributes to neuronal damage in several neurodegenerative diseases including Alzheimer's disease, prion diseases, Parkinson's disease, multiple sclerosis, and Huntington's disease [5], [7]. In prion diseases and other neurodegenerative disorders, microglia can become overactivated and release ROS, NO, and cytokines, which might cause vascular damage in addition to neurodegeneration [7], [8], [9], [10]. Pattern recognition receptors expressed on the microglial surface, including Toll-like receptors and scavenger receptors seem to associate physically to form a receptor complex, which is one of the primary, common pathways through which diverse toxin signals are transduced into ROS production in microglia [4], [11].…”
Section: Introductionmentioning
confidence: 99%